1959
DOI: 10.4141/cjps59-063
|View full text |Cite
|
Sign up to set email alerts
|

A STUDY OF THE MEGAGAMETOPHYTE IN PRUNUS AVIUM AND ITS RELATION TO FRUIT SETTING

Abstract: A cytological study of the megagametophyte in Prunus avium was undertaken to determine to what extent delayed development, cytological irregularities, or degeneration might account for failure of this fruit to set commercial crops. In 1957, under high temperatures, the proportion of embryo sacs with functional egg cells decreased rapidly following anthesis. In 1958, under low temperatures, the maximum proportion of functional embryo sacs at any one time was much lower than in 1957, and the proportion of embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 1 publication
0
18
0
1
Order By: Relevance
“…Ovule longevity may even be shorter, e.g. in some apricot cultivars with a larger number of degenerated embryo sacs, it may only occur until day 2 from the onset of full bloom (Eaton, 1959). Contrary to these data, in pear cv.…”
Section: Discussionmentioning
confidence: 80%
“…Ovule longevity may even be shorter, e.g. in some apricot cultivars with a larger number of degenerated embryo sacs, it may only occur until day 2 from the onset of full bloom (Eaton, 1959). Contrary to these data, in pear cv.…”
Section: Discussionmentioning
confidence: 80%
“…(1983) found that low temperatures during apple bud development period can, when imposed artificially, increase fruit set and that female flower fertility is involved. Eaton (1959) working with sweet cherry at two locations found that where mean temperatures were 4 K lower a few days before anthesis, there was a delay in megagametophyte development as compared with the external parts of the flower. Differences between apricot and other species could be genetic in origin or due to differences in climatic conditions at the experimental location.…”
Section: Discussionmentioning
confidence: 99%
“…Dorsey (1929) found that unfavourable cultural conditions delay development of the embryo sac. Apparently, low temperatures before anthesis inhibit development of the external parts of the flower (Eaton, 1959). Williams (1965) found that summer nitrogen applications produced flowers capable of fertilization for almost twice as long as those of normal flowers.…”
mentioning
confidence: 99%
“…6, Table 5). At anthesis, Eaton (1959) observed that many embryo sacs had reached the eightnucleate stage, and then 50% and 80% degenerated 2 and 4 days after anthesis, respectively, in 'Windsor' sweet cherry grown in Ohio, where the average daily maximum temperature from bud burst to petal fall was as high as 23°C. In our observations, half of the embryo sacs of 'Satohnishiki' had reached the eight-nucleate stage at anthesis both in Kagawa and Yamagata.…”
mentioning
confidence: 99%